10-Minute Targeted Geriatric Assessment Predicts Disability and Hospitalization in Fast-Paced Acute Care Settings. (6th May 2019) - Aliberti, Márlon J R; Covinsky, Kenneth E; Apolinario, Daniel; Smith, Alexander K; Lee, Sei J; Fortes-Filho, Sileno Q; Melo, Juliana A; Souza, Natalia P S; Avelino-Silva, Thiago J; Jacob-Filho, Wilson
Abstract: Background: Limited time and resources hinder the use of comprehensive geriatric assessment in acute contexts. We investigated the predictive value of a 10-minute targeted geriatric assessment (10-TaGA) for adverse outcomes over 6 months among acutely ill older outpatients. Methods: Prospective study comprising 819 acutely ill outpatients (79.2 ± 8.4 years; 63% women) in need of intensive management (eg, intravenous therapy, laboratory test, radiology) to avoid hospitalization. The 10-TaGA provided a validated measure of cumulative deficits. Previously established 10-TaGA cutoffs defined low (0–0.29), medium (0.30–0.39), and high (0.40–1) risks. To estimate whether 10-TaGA predicts new dependence in activities of daily living and hospitalization over the next 6 months, we used hazard models (considering death as competing risk) adjusted for standard risk factors (sociodemographic factors, Charlson comorbidity index, and physician estimates of risk). Differences among areas under receiver operating characteristic curves (AUROC) examined whether 10-TaGA improves outcome discrimination when added to standard risk factors. Results: Medium- and high-risk patients, according to 10-TaGA, presented a higher incidence of new activities of daily living dependence (21% vs 7%, adjusted subhazard ratio [aHR] = 2.4, 95% CI = 1.3–4.5; 40% vs 7%, aHR = 5.0, 95% CI = 2.8–8.7, respectively) and hospitalization (27% vs 13%, aHR = 2.0, 95% CI = 1.2–3.3; 37% vs 13%, aHR = 2.9, 95% CI = 1.8–4.6, respectively) than low-risk patients. The 10-TaGA remarkably improved the discrimination of models that incorporated standard risk factors to predict new activities of daily living dependence (AUROC = 0.76 vs 0.71, p < .001) and hospitalization (AUROC = 0.71 vs 0.68, p < .001). Conclusions: The 10-TaGA is a practical and efficient comprehensive geriatric assessment tool that improves the prediction of adverse outcomes among acutely ill older outpatients.